2003
DOI: 10.1063/1.1562608
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy relaxation of aqueous azide ion confined in reverse micelles

Abstract: Vibrational energy relaxation (VER) times have been measured by ultrafast infrared spectroscopy near 2000 cm−1 for the antisymmetric stretching ν3 band of azide ion in water pools of nonionic reverse micelles (RM). The water pool radii were varied in the 1–3 nm range by adjusting the water-to-surfactant molar ratio, ω=[H2O]/[surfactant]. Compared to the value measured in this work for bulk water (0.81±0.06 ps), the VER decay times are about three times longer (2.5±0.2 ps) for the smallest RM studied (ω=1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 74 publications
(100 reference statements)
5
114
2
Order By: Relevance
“…On the other hand, for polyatomic cases, Hochstrasser and coworkers reported that the vibrational relaxation of azide ion takes place in 1.2 ps in H 2 O and 2.4 ps in D 2 O [1,2]. Very recently, Zhong et al [18] reported that the vibrational relaxation time is 0.81 ps in H 2 O. Morita and Kato [19] performed theoretical calculation of the vibrational relaxation process for N À 3 in water. They considered the intramolecular charge fluctuation induced by the solute vibrational motion and by the external potential by the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for polyatomic cases, Hochstrasser and coworkers reported that the vibrational relaxation of azide ion takes place in 1.2 ps in H 2 O and 2.4 ps in D 2 O [1,2]. Very recently, Zhong et al [18] reported that the vibrational relaxation time is 0.81 ps in H 2 O. Morita and Kato [19] performed theoretical calculation of the vibrational relaxation process for N À 3 in water. They considered the intramolecular charge fluctuation induced by the solute vibrational motion and by the external potential by the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…31,39,40 Infrared (IR) pumpprobe experiments on the azide ion confined in reverse micelles have measured the azide ion vibrational lifetime. 41 A significant increase of the lifetime of the azide ion is observed for the smallest reverse micelles. Polarization-resolved pump-probe studies of the same system showed that the orientational relaxation of azide was at least an order of magnitude slower than the reported lifetimes, which was interpreted as suggesting restricted mobility of water in reverse micelles.…”
Section: Introductionmentioning
confidence: 94%
“…Other studies, in particular NMR experiments and vibrational energy relaxation of probe molecules, support this observation. 23,51 From our study, we conclude that there is no water between the PEO chains, for these small reverse micelles as represented in Figure 12. However, we observe that for w • = 15, S deviates a lot from the fit.…”
Section: T(k)mentioning
confidence: 58%
“…The conformation of the hydrophilic polyethylene oxide (PEO) chain in nonionic reverse micelles is still a matter of controversy. 23,31,51,52 Numerous papers depict the structure of a nonionic reverse micelle. Mostly, they show that the PEO chain penetrates the water volume and dangles freely in the water body.…”
Section: T(k)mentioning
confidence: 99%
See 1 more Smart Citation